A Batch Study on Removal of Heavy Metals Using Laterite Soil-Pressmud in Landfill Leachate - A. Harlina; M. Maheera; I. Norli (Iranica Journal of Energy and Environment, 2016)
This batch study focuses on suitability of laterite soil-pressmud as daily soil cover of landfill.  The laterite soil samples were mixed with waste from sugar refinery process, namely pressmud at different percentages of weight ratio (10, 30 and 50%). The batch equilibrium tests were carried out and glaringly showed that the laterite soil-pressmud mixtures have the capability to remove more than 62% of Cr, Cu, Mn, Ni, Pb and Zn concentration in leachate. Meanwhile, the removal efficiency of heavy metals from leachate in the laterite soil alone was lower than 50%. Pressmud alone however showed more than 53% removal. The laterite soil-pressmud mixtures, particularly at 30 and 50 percent of pressmud signify great potential as daily soil cover in reduction of heavy metals migration in landfill leachate.